Monte Carlo and molecular dynamics simulations of screw dislocation locking by Cottrell atmospheres in low carbon Fe–C alloys. (November 2015) - Veiga, R.G.A.; Goldenstein, H.; Perez, M.; Becquart, C.S.
Graphical abstract: Abstract: On-lattice Monte Carlo shows strong carbon segregation at a screw dislocation in bcc iron for carbon contents that vary from 20 to 500 ppm, typical in ultra low and low carbon steels. Molecular dynamics simulations are then carried out using the atomic coordinates of equilibrated Cottrell atmospheres. The stresses required to make the screw dislocation break free of the carbon cloud are very high compared to carbon in solid solution; the locking time is also much longer. All simulations are performed at 300 K.